Iron-poor manganese zinc ferrite material and preparation method thereof
By adjusting the formulation and preparation process of iron-bearing manganese-zeb ferrite materials, the problem of reducing magnetic permeability of existing materials at low temperatures is solved, and high permeability and high frequency and high impedance at high Curie temperatures and low temperatures are achieved. Performance, suitable for more stringent application environments.
Patent Information
- Application Number
- CN202411609260.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing iron-leaved manganese-zeb ferrite materials cannot maintain high magnetic permeability at low temperatures while maintaining high Curie temperatures, and cannot meet the needs of use in low temperature environments.
By adjusting the content ratio of Fe2O3, ZnO, Mn3O4, CaCO3 and Co2O3, a ferro-leaved manganese-zeb ferrite material is prepared, including the main and auxiliary components, using wet ball milling, pre-firing, secondary grinding, granulation, By forming and sintering, materials with high magnetic permeability and high Curie temperature are produced.
It achieves a high magnetic permeability at -40℃, and the Curie temperature reaches above 160℃, meeting higher ambient temperature requirements and ensuring the working efficiency of the material under lower and higher temperature conditions.
Smart Images

Figure BDA0005130520830000091 
Figure BDA0005130520830000092 
Figure BDA0005130520830000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ferrite preparation, and in particular to an iron-poor manganese-zinc ferrite material and a preparation method thereof. Background Art
[0002] In recent years, with the beginning of the third industrial revolution and the development of science and technology, human beings have gradually entered the electronic information age, and electronic products have become indispensable for human work, office, leisure, entertainment, study, video conferencing, etc. While electronic products bring convenience to human beings, they also bring certain environmental pollution-electromagnetic interference. High permeability manganese zinc ferrite is widely used in signal transmission and its anti-electromagnetic interference technology, but high permeability manganese zinc ferrite material has high permeability, low resistivity, low cut-off frequency, and can only be used in low frequency bands; nickel zinc ferrite has high resistivity, high cut-off frequency, high frequency and high impedance, and is widely used in high frequency band filtering. The disadvantages are low permeability, poor low frequency filtering, and high price; although nanocrystalline materials can be used in low frequency band and high frequency band filtering fields, nanocrystalline materials can only make simple-shaped magnetic cores and the cost is high, so the usage is not large. For the above reasons, scientists discovered the poor iron manganese zinc ferrite material, which has the advantages of high permeability, high Curie temperature, high frequency and high impedance, and low price, and has been favored by customers.
[0003] At present, only a few companies have achieved mass production of poor iron manganese zinc ferrite materials. For example, JPZ-4 material of Anci has a magnetic permeability of 4000 and a Curie temperature of >105℃. The magnetic permeability is high, but the Curie temperature is low and the application range is small. The magnetic permeability of DMR31 material of Dongmei is 2000 and the Curie temperature is 160℃, but the magnetic permeability is only 750 at low temperature of -40℃. The magnetic permeability of Tiantong Ti30 material is 3000 and the Curie temperature is only 130℃.
[0004] Chinese invention patent CN110156451B authorizes a high-impedance iron-poor manganese-zinc ferrite material. By limiting the content of iron oxide to 46-49.8 mol%, the content of zinc oxide to 17-23 mol%, and the rest being manganese oxide, the magnetic permeability μi of the manganese-zinc ferrite material is achieved to be 2500±25%, and it has good high-impedance performance under 1MHz~500MHz conditions.
[0005] Chinese invention patent CN115650715A discloses a broadband high-impedance and high-resistivity manganese-zinc ferrite material. By limiting the content of iron oxide to 40.5-45.5 mol%, the content of manganese oxide to 36-40 mol%, and the rest being zinc oxide, the broadband high-impedance and high-resistivity of the manganese-zinc ferrite material is achieved.
[0006] Chinese invention patent CN111138180A discloses a wide temperature range high magnetic permeability manganese-zinc ferrite material. By limiting the content of iron oxide to 46-50 mol%, the content of zinc oxide to 9-12.9 mol%, and the rest being manganese oxide, the manganese-zinc ferrite has a magnetic permeability of >1000, a Curie temperature greater than 180°C, and a wide-band high impedance performance.
[0007] In order to cope with harsh application environments, electronic products are required to maintain a high magnetic permeability at low temperatures (such as -40°C) to ensure the working efficiency and stability of the equipment. Taking the magnetic permeability of the standard room temperature of 25°C as the standard, when the manganese-zinc ferrite material is generally reduced from 25°C to -40°C, the magnetic permeability has been reduced to less than 50% of the standard room temperature magnetic permeability, which greatly reduces the working efficiency of the manganese-zinc ferrite material at low temperatures and cannot meet the use requirements in special environments. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the defect of the prior art poor iron manganese zinc ferrite material that it cannot maintain high magnetic permeability at low temperature while having a high Curie temperature, thereby providing a poor iron manganese zinc ferrite material and a preparation method thereof.
[0009] To this end, the present invention provides an iron-poor manganese-zinc ferrite material, including a main component and an auxiliary component. Taking the total weight of the main component as 100wt%, the main component includes: Fe2O3 of 65-67wt%, ZnO of 10-12wt%, and the rest of Mn3O4; based on the total weight of the main component, the auxiliary component includes 100-2000ppm CaCO3 and 1000-10000ppm Co2O3.
[0010] Furthermore, the magnetic permeability of the iron-poor manganese-zinc ferrite material at -40°C and 25°C is 1600-2400.
[0011] Furthermore, the Curie temperature of the iron-poor manganese-zinc ferrite material is above 160°C.
[0012] In the second aspect, the present invention also provides a method for preparing the iron-poor manganese-zinc ferrite material described in any of the above, comprising mixing Fe2O3, ZnO, and Mn3O4 in proportion, grinding the mixture once, pre-burning it to obtain a pre-burned material, mixing the pre-burned material with auxiliary components, and grinding the mixture a second time, granulating, molding, and sintering it to obtain the iron-poor manganese-zinc ferrite material.
[0013] Furthermore, the primary grinding is wet ball milling. Preferably, the wet ball milling time is 30-120 min. Preferably, during the wet ball milling process, the mass ratio of the grinding medium, the mixture and water is 4:0.8-1.2:0.8-1.2.
[0014] Furthermore, the pre-burning temperature is 980-1035° C., and the speed is 400-500 kg / h.
[0015] The pre-firing is carried out in a rotary kiln, and the pre-firing speed refers to the speed at which the car enters the furnace.
[0016] Furthermore, the secondary grinding further includes the step of mixing a binder and a dispersant;
[0017] Preferably, the adhesive comprises PVA adhesive;
[0018] Preferably, the dispersant comprises citric acid;
[0019] Preferably, the binder accounts for 5-10wt% of the total mass of the pre-sintered material;
[0020] Preferably, the dispersant accounts for 1-2 wt % of the total mass of the pre-sintered material.
[0021] Furthermore, the secondary grinding is wet ball milling. Preferably, the wet ball milling time is 120-150 min. Preferably, during the wet ball milling process, the mass ratio of the grinding medium, the mixture and water is 4:0.8-1.2:0.8-1.2.
[0022] Further, the sintering is carried out at 1300-1400°C for 4-10 hours under the condition of controlling the oxygen content to 3-21 vol% in a mixed atmosphere of nitrogen and air or oxygen, and cooling is carried out under the equilibrium oxygen partial pressure; preferably, the sintering is carried out at 1320-1340°C for 6-8 hours under the condition of controlling the oxygen content to 20-21 vol% in a mixed atmosphere of nitrogen and air or oxygen, and cooling is carried out under the equilibrium oxygen partial pressure.
[0023] The equilibrium oxygen partial pressure in the method of the present invention is calculated according to the formula lg(P(O2))=ab / T, wherein a is 5-10, b is 10000-15000, and T is the absolute temperature.
[0024] Furthermore, the granulation is spray granulation; and / or the molding is compression molding.
[0025] The technical solution of the present invention has the following advantages:
[0026] 1. The iron-poor manganese-zinc ferrite material provided by the present invention comprises a main component and an auxiliary component. Taking the total weight of the main component as 100wt%, the main component comprises: 65-67wt% of Fe2O3, 10-12wt% of ZnO, and the rest of Mn3O4; the auxiliary component comprises 100-2000ppm of CaCO3 and 1000-10000ppm of Co2O3, and the iron-poor manganese-zinc ferrite material of the present invention has the characteristics of low temperature high magnetic permeability, high Curie temperature and high frequency high impedance by controlling the contents of Fe2O3, ZnO, Mn3O4, CaCO3 and Co2O3 in the formula within the above range, so that the iron-poor manganese-zinc ferrite material has good filtering effect at low temperature of -40℃. At the same time, the Curie temperature of 160℃ can meet higher ambient temperature requirements and ensure that the material works under lower and higher temperature conditions.
[0027] Generally, the anisotropy constant of spinel ferrite is negative, while the anisotropy constant of CoO is K1>0. After the addition of Co2O3, K1 approaches 0, which is beneficial to the improvement of magnetic permeability.
[0028] 2. The iron-poor manganese-zinc ferrite material provided by the present invention comprises mixing Fe2O3, ZnO and Mn3O4 in proportion, grinding the mixture once, pre-burning to obtain a pre-burned material, mixing the pre-burned material with auxiliary components, grinding the mixture twice, granulating, molding and sintering to obtain the iron-poor manganese-zinc ferrite material. The preparation method is simple, easy to operate and suitable for industrial production, wherein the sintering is sintering at 1300-1400°C for 4-10 hours under the condition of controlling the oxygen content to 3-21 vol% in a nitrogen atmosphere, and cooling at a balanced oxygen partial pressure; preferably, the sintering is sintering at 1320-1340°C for 6-8 hours under the condition of controlling the oxygen content to 20-21 vol% in a nitrogen atmosphere, and cooling at a balanced oxygen partial pressure; under the above sintering conditions, an iron-poor manganese-zinc ferrite material with better performance can be obtained. DETAILED DESCRIPTION
[0029] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0030] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0031] Example 1
[0032] This embodiment provides an iron-poor manganese-zinc ferrite material and a preparation method thereof, comprising the following steps:
[0033] (1) Ingredients: Fe2O3: 66.4wt%, Mn3O4: 22.6wt%, ZnO: 11wt% are weighed as the main component. Based on the total mass of the main component, 200ppm of CaCO3 and 7000ppm of Co2O3 are weighed as the auxiliary component.
[0034] (2) Primary grinding: Add steel balls and water to the main component in a ball mill and mix for 30 minutes, wherein the mass ratio of steel balls to main component and water is 4:1:1.
[0035] (3) Pre-burning: The slurry after removing the steel balls is sprayed into a rotary kiln through a spray gun and pre-burned at 1020° C. at a rate of 450 kg / h to obtain a pre-burned material.
[0036] (4) Secondary grinding: 400 kg of pre-burned material was weighed and put into a sand mill. Then, 200 ppm of CaCO3, 7000 ppm of Co2O3, 32 kg of glue PVA and 6 kg of dispersant citric acid were added to obtain a mixture. Steel balls and water were added and ball milled for 150 min. The mass ratio of steel balls, mixture and water was 4:1:1.
[0037] (5) Granulation and molding: The ball-milled slurry is subjected to component analysis correction and then spray granulation to obtain ferrite particles; the ferrite particles are pressed into blank samples of H25×15×8.
[0038] (6) Sintering: Sintering at 1330°C for 7 hours under the conditions of N2 content of 79 vol% and oxygen content of 21 vol%. The cooling stage is carried out under balanced oxygen partial pressure to obtain a magnetic core.
[0039] Example 2
[0040] This embodiment provides an iron-poor manganese-zinc ferrite material and a preparation method thereof, comprising the following steps:
[0041] (1) Ingredients: The components are weighed in a weight ratio of 66.4 wt% Fe2O3, 22.6 wt% Mn3O4, and 11 wt% ZnO as the main component. Based on the total mass of the main component, the components are weighed in a weight ratio of 1200 ppm CaCO3 and 6000 ppm Co2O3 as the auxiliary component.
[0042] (2) Primary grinding: The main components were mixed in a ball mill for 60 min, wherein the mass ratio of steel balls, mixture and water was 4:1.2:1.2.
[0043] (3) Pre-burning: The slurry after removing the steel balls is sprayed into a rotary kiln through a spray gun and pre-burned at 1020° C. at a rate of 450 kg / h to obtain a pre-burned material.
[0044] (4) Secondary grinding: 400 kg of pre-burned material was weighed and put into a sand mill, and then auxiliary components, 40 kg of glue PVA and 4 kg of dispersant citric acid were added, and ball milled for 120 min, wherein the mass ratio of steel ball, mixture and water was 4:1:1.
[0045] (5) Granulation and Molding After the ball-milled slurry is subjected to component analysis correction, it is spray granulated to obtain ferrite particles; the ferrite particles are pressed into a blank sample of H25×15×8.
[0046] (6) Sintering: Sintering at 1340°C for 7 hours under the conditions of N2 content of 80 vol% and oxygen content of 20 vol%. The cooling stage is carried out under balanced oxygen partial pressure to obtain a magnetic core.
[0047] Example 3
[0048] The present embodiment provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Embodiment 1 is that in step (1), the main components are in the following proportions: Fe2O3: 66.2wt%, Mn3O4: 23wt%, ZnO: 10.8wt%, and each component is weighed as an auxiliary component in a weight ratio of 200ppm CaCO3 and 8000ppm Co2O3 based on the total mass of the main components.
[0049] Example 4
[0050] The present embodiment provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Embodiment 1 is that in step (1), the main components are in the following proportions: Fe2O3: 65.8wt%, Mn3O4: 23.8wt%, ZnO: 10.4wt%, and each component is weighed as an auxiliary component in a weight ratio of 200ppm CaCO3 and 10000ppm Co2O3 based on the total mass of the main components.
[0051] Example 5
[0052] This embodiment provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Embodiment 1 is that the sintering temperature and time are different. In this embodiment, the sintering is performed at 1300° C. for 9 hours.
[0053] Example 6
[0054] This embodiment provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Embodiment 1 is that the sintering temperature and time are different. In this embodiment, the sintering is performed at 1350° C. for 5 hours.
[0055] Example 7
[0056] This embodiment provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Embodiment 1 is that the CaCO3 content in step (1) is different. In this embodiment, the weight ratio of CaCO3 in the auxiliary component is 100 ppm based on the total mass of the main component.
[0057] Comparative Example 1
[0058] This comparative example provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Example 1 is that the content of the main component in step (1) is different. The main components in this comparative example are in the following proportions: Fe2O3: 66.4wt%, Mn3O4: 21.1wt%, ZnO: 12.5wt%.
[0059] Comparative Example 2
[0060] This comparative example provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Example 1 is that the content of the main component in step (1) is different. The main components in this comparative example are in the following proportions: Fe2O3: 66.4wt%, Mn3O4: 24.2wt%, ZnO: 9.4wt%.
[0061] Comparative Example 3
[0062] This comparative example provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Example 1 is that the content of the main component in step (1) is different. The main components in this comparative example are in the following proportions: Fe2O3: 64.3wt%, Mn3O4: 24.7wt%, ZnO: 11wt%.
[0063] Comparative Example 4
[0064] This comparative example provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Example 1 is that the content of the main component in step (1) is different. The main components in this comparative example are in the following proportions: Fe2O3: 68wt%, Mn3O4: 21wt%, ZnO: 11wt%.
[0065] Comparative Example 5
[0066] This comparative example provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Example 1 is that the Co2O3 content in step (1) is different. In this comparative example, the weight ratio of Co2O3 in the auxiliary component is 500ppm based on the total mass of the main component.
[0067] Comparative Example 6
[0068] This comparative example provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Example 1 is that the Co2O3 content in step (1) is different. In this comparative example, the weight ratio of Co2O3 in the auxiliary component is 15000 ppm based on the total mass of the main component.
[0069] Comparative Example 7
[0070] This comparative example provides an iron-poor manganese-zinc ferrite material and a preparation method thereof. The difference from Example 1 is that the CaCO3 content in step (1) is different. In this comparative example, the weight ratio of CaCO3 in the auxiliary component is 2500ppm based on the total mass of the main component.
[0071] The initial magnetic permeability μi and Curie temperature of the iron-poor manganese-zinc ferrite materials prepared in various embodiments and comparative examples were tested at room temperature and at -40°C. The test conditions were frequency f=10kHz and voltage u=0.25V. The results are shown in Table 1 below.
[0072] Table 1 Performance test results
[0073]
[0074] Table 2 Performance test results
[0075]
[0076]
[0077] It can be seen from the results in the above table that, compared with Comparative Examples 2, 4-7, the iron-poor manganese-zinc ferrite materials prepared in each embodiment of the present invention not only significantly improve the low-temperature magnetic permeability, but also take into account the Curie temperature above 160°C, and can take into account the characteristics of low-temperature high magnetic permeability, high Curie temperature and high-frequency high impedance. Compared with Comparative Examples 1 and 3, the Curie temperature of the iron-poor manganese-zinc ferrite materials prepared in each embodiment of the present invention is significantly improved.
[0078] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. An iron-poor manganese-zinc ferrite material, characterized in that: The iron-poor manganese-zinc ferrite material includes a main component and an auxiliary component. Taking the total weight of the main component as 100wt%, the main component includes: Fe2O3 is 65-67wt%, ZnO is 10-12wt%, and the rest is Mn3O4; based on the total weight of the main component, the auxiliary component includes 100-2000ppm CaCO3 and 1000-10000ppm Co2O3.
2. The iron-poor manganese-zinc ferrite material according to claim 1, characterized in that: The initial magnetic permeability of the iron-poor manganese-zinc ferrite material at -40°C and 25°C is 1600-2400.
3. The iron-poor manganese-zinc ferrite material according to claim 1 or 2, characterized in that: The Curie temperature of the iron-poor manganese-zinc ferrite material is above 160°C.
4. A method for preparing the iron-poor manganese-zinc ferrite material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing Fe2O3, ZnO and Mn3O4 in proportion, grinding the mixture once, pre-burning the mixture to obtain a pre-burned material, mixing the pre-burned material with auxiliary components, grinding the mixture twice, granulating, molding and sintering the mixture to obtain an iron-poor manganese-zinc ferrite material.
5. The method for preparing the iron-poor manganese-zinc ferrite material according to claim 4, characterized in that: The primary grinding is wet ball milling. Preferably, the wet ball milling time is 30-120 min. Preferably, during the wet ball milling process, the mass ratio of the grinding medium, the mixture and water is 4:0.8-1.2:0.8-1.
2.
6. The method for preparing the iron-poor manganese-zinc ferrite material according to claim 4, characterized in that: The pre-burning temperature is 980-1035° C., and the speed is 400-500 kg / h.
7. The method for preparing the iron-poor manganese-zinc ferrite material according to claim 4, characterized in that: The secondary grinding also includes the step of mixing a binder and a dispersant; Preferably, the adhesive comprises PVA adhesive; Preferably, the dispersant comprises citric acid; Preferably, the binder accounts for 5-10wt% of the total mass of the pre-sintered material; Preferably, the dispersant accounts for 1-2 wt % of the total mass of the pre-sintered material.
8. The method for preparing the iron-poor manganese-zinc ferrite material according to claim 4 or 7, characterized in that: The secondary grinding is wet ball milling. Preferably, the wet ball milling time is 120-150 min. Preferably, during the wet ball milling process, the mass ratio of the grinding medium, the mixture and water is 4:0.8-1.2:0.8-1.
2.
9. The method for preparing the iron-poor manganese-zinc ferrite material according to claim 4, characterized in that: The sintering is carried out at 1300-1400°C for 4-10 hours under the condition of controlling the oxygen content to 3-21 vol% in a mixed atmosphere of nitrogen and air or oxygen, and cooling is carried out under the equilibrium oxygen partial pressure; preferably, the sintering is carried out at 1320-1340°C for 6-8 hours under the condition of controlling the oxygen content to 20-21 vol% in a mixed atmosphere of nitrogen and air or oxygen, and cooling is carried out under the equilibrium oxygen partial pressure.
10. The method for preparing the iron-poor manganese-zinc ferrite material according to any one of claims 4 to 9, characterized in that: The granulation is spray granulation; and / or the molding is compression molding.
Citation Information
Patent Citations
A high-impedance iron-poor manganese-zinc ferrite material and its preparation method
CN110156451B
Broadband high-impedance manganese-zinc ferrite material and preparation method thereof
CN111138180A
Broadband high-impedance high-resistivity manganese zinc ferrite material and preparation method thereof
CN115650715A
Broadband high impedance MnZn ferrite material and manufacture method thereof
CN101857426A
Manganese-zinc ferrite material with wide temperature range and low temperature coefficient and preparation method thereof
CN102108022A